REASONS FOR SUPERSEDEAS IMPLEMENTING - R. G. Bikmiyev (Russian Journal of Economics and Law)
On court practice examples and statistical data the article views the grounds for supersedes implementing. The research shows the necessity of the further study and detailed normative-legal regulation of such means of procedural compulsion as supersedes, due to underestimation of its efficiency and significance by the preliminary investigation bodies.